Ex vivo Evaluation of a New Drill System for Placement of Percutaneous Bone Conduction Devices - Strijbos, Ruben M.; Straatman, Louise V.; Stokroos, Robert J.; Johansson, Martin L. (Frontiers in Surgery, 2022)
The procedure for installation of a percutaneous bone-conducting device has undergone significant improvements since its introduction 40 years ago. Today, the linear incision technique with tissue preservation (LITT-P) and the minimally invasive procedure (MIPS) are the most commonly used approaches. In both these techniques, a gradual increase of the osteotomy using a three-step drilling sequence is utilized, as this approach can allow a stepwise deepening and widening of the osteotomy in the mastoid and can prevent bone overheating. A new minimally invasive procedure (MONO) has been developed that allows an osteotomy to be performed and enables complete removal of the bone volume in one single drill step for a 4 mm implant using a novel parabolic twist drill. Here, the feasibility of the MONO procedure was qualitatively and quantitatively evaluated in terms of the dura response to drill trauma in comparison with the outcomes achieved with guide drills used for the LITT-P and MIPS techniques. Fresh frozen temporal bone from a human cadaver was subjected to penetration by three drills beyond the base of the mastoid bone to different depths. The sites were evaluated, and the damage to and possible penetration of the dura were determined. The results showed that for a drill depth exceeding mastoid bone thickness by not more than 1 mm, damage to the dura was limited or nonexistent, whereas for a drill depth exceeding bone thickness by 2 mm, damage increased, or the dura was penetrated. There was a trend toward more damage and penetration for both the round burr and MIPS guide drill compared with the MONO drill bit. From this experimental ex vivo study, it can be concluded that if the dura is encountered, the MONO system is not more inclined to penetrate the dura than the conventional LITT-P and MIPS systems.